Phosphorous bonding in single wall carbon nanotubes studied by X-ray photoelectron spectroscopy and DFT calculations. (April 2016) - Araujo, Joyce R.; Silva, Alexander M.; Gouvêa, Cristol P.; Lopes, Eluise S.; Santos, Ramon A.A.; Terrazos, L.A.; Capaz, Rodrigo B.; Achete, Carlos A.; Maciel, Indhira O.
Abstract: Phosphorous-doped single wall carbon nanotubes were synthesized by an aerosol-assisted chemical vapor deposition by adding triphenilphosphine in the ethanol-ferrocene precursor solution. X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy were carried out along with density functional theory (DFT) calculations in order to understand the nature of phosphorous chemical doping. Binding energies of P 2p electrons, experimentally measured by XPS, are 129.6 eV and 134.3 eV. DFT calculations allow for the assignment of these levels to substitutional phosphorous and phosphorous-oxygen groups, respectively. The nature of phosphorous doping is elucidated through band structure and density of states calculations.